2013
DOI: 10.1017/jse.2013.3
|View full text |Cite
|
Sign up to set email alerts
|

Transition and Students With Twice Exceptionality

Abstract: Twice exceptional is one of the terms used to describe students who have giftedness and a disability. This is a small heterogeneous population of individual learners who are underserved in special, gifted, and mainstream education settings. Despite the availability of research on transition for students with disabilities there is little research or literature available on transition for students who experience twice exceptionality (2E). This paper provides a review of the literature available on 2E, taking a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
0
6
0
4
Order By: Relevance
“…While these are both literature‐based, only Hughes et al () state that they carried out a systematic literature review. Both focus on one specific aspect of the transition to secondary school, with Hughes et al () considering the impact of transition on children’s psychosocial development, and Prior () focusing on children with ‘twice exceptionality’, as defined above. The current article therefore makes an original contribution to the existing body of literature through focusing on the wider population of children with an ASN and the preparation for and process of the transition to secondary school.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…While these are both literature‐based, only Hughes et al () state that they carried out a systematic literature review. Both focus on one specific aspect of the transition to secondary school, with Hughes et al () considering the impact of transition on children’s psychosocial development, and Prior () focusing on children with ‘twice exceptionality’, as defined above. The current article therefore makes an original contribution to the existing body of literature through focusing on the wider population of children with an ASN and the preparation for and process of the transition to secondary school.…”
Section: Methodsmentioning
confidence: 99%
“…Two literature reviews that focused on the transition to secondary school for children with ASN were identified (Hughes et al, 2013;Prior, 2013). While these are both literature-based, only Hughes et al (2013) state that they carried out a systematic literature review.…”
Section: Existing Literature Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of recognition of the three participants’ areas of learning strength was a finding common to research studies on academic provision for twice-exceptional learners (Foley Nicpon et al, 2011; Schultz, 2012; Willard-Holt et al, 2013). Transfer to high school presents new opportunities for individuals to be identified for specialized learning programs and opportunities (Prior, 2013). Student engagement is critical to motivating students to achieve at school, influenced by many factors including the perceived relevance and appropriateness of the opportunities available and, as such, “engagement is malleable by the actions of teachers” (Gibbs & Poskitt, 2010, p. 12).…”
Section: Discussionmentioning
confidence: 99%
“…More critically for vulnerable learners, there were “limited or no opportunities to develop awareness of their strengths and abilities” and these students were therefore “at risk” (p.2) during this time. A more recent review of the international literature (Prior, 2013) found little research aimed specifically at investigating the experiences of twice-exceptional students during transfer. However, more generalized research suggested that education professionals should focus on providing vulnerable learners with individualized assistance during the transfer process to improve educational outcomes (Ministry of Education, 2010; Wylie et al, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%